2021
DOI: 10.3390/ijms22136673
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Wnt16 Leads to Skeletal Deformities and Downregulation of Bone Developmental Pathway in Zebrafish

Abstract: Wingless-type MMTV integration site family, member 16 (wnt16), is a wnt ligand that participates in the regulation of vertebrate skeletal development. Studies have shown that wnt16 can regulate bone metabolism, but its molecular mechanism remains largely undefined. We obtained the wnt16-/- zebrafish model using the CRISPR-Cas9-mediated gene knockout screen with 11 bp deletion in wnt16, which led to the premature termination of amino acid translation and significantly reduced wnt16 expression, thus obtaining th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 58 publications
(68 reference statements)
1
20
2
Order By: Relevance
“…In our study, phenotypes in wnt16 -/- mutant larvae were indistinguishable for three different alleles. Moreover, wnt16 -/- mutants did not exhibit loss of caudal fin rays, in agreement with a wnt16 presumptive null allele generated by McGowan et al (McGowan et al, 2021), and contrasting with the allele of Qu et al (Qu et al, 2021). The allele of Qu et al comprised a 11bp deletion in exon 3, which was generated by two gRNAs with different target sites.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In our study, phenotypes in wnt16 -/- mutant larvae were indistinguishable for three different alleles. Moreover, wnt16 -/- mutants did not exhibit loss of caudal fin rays, in agreement with a wnt16 presumptive null allele generated by McGowan et al (McGowan et al, 2021), and contrasting with the allele of Qu et al (Qu et al, 2021). The allele of Qu et al comprised a 11bp deletion in exon 3, which was generated by two gRNAs with different target sites.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have reported disparate skeletal phenotypes in zebrafish homozygous for presumptive wnt16 null alleles; for example, Qu et al reported loss of caudal fin rays, whereas caudal fin rays in mutants described by McGowan et al are intact (McGowan et al, 2021; Qu et al, 2021). To help resolve these discrepancies, we generated multiple wnt16 loss-of-function alleles using CRISPR/Cas9-based gene editing (Supplemental Fig 2A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated that despite normal bone healing, the recruitment of osteoblasts was compromised in mutants during the early stages of repair [ 95 ]. While McGowan et al focused on bone fractures, Qu et al studied the skeletal structure of a second wnt16 mutant, reporting reduced bone density, curved spines and abnormal jaw [ 96 ]. The same group performed RNA-seq, identifying differentially expressed genes associated with mTOR, FoxO and VEGF pathways [ 96 ].…”
Section: Zebrafish As Animal Models To Accelerate Discoveries Of Huma...mentioning
confidence: 99%
“…While McGowan et al focused on bone fractures, Qu et al studied the skeletal structure of a second wnt16 mutant, reporting reduced bone density, curved spines and abnormal jaw [ 96 ]. The same group performed RNA-seq, identifying differentially expressed genes associated with mTOR, FoxO and VEGF pathways [ 96 ]. Finally, recent work by Watson et al interrogated the biology behind the pleiotropy at the locus (which was associated with BMD and lean mass) [ 97 ].…”
Section: Zebrafish As Animal Models To Accelerate Discoveries Of Huma...mentioning
confidence: 99%